News media representation of China’s family planning policy in China daily: a corpus-assisted critical discourse analysis - Wang Can,; Mohammad Fadzeli Jaafar,; Anis Nadiah Che Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
China has implemented the universal two-child policy and three-child policy in response to the demographic challenges brought about by the aging population and low fertility rate. The implementation of these policies relies on the support of various societal subsystems, with newspapers playing a significant role in their publicity and interpretation. However, little attention has been paid to how these policies are linguistically represented in Chinese English-language newspapers. Therefore, the present study intends to conduct a corpus-assisted critical discourse analysis by identifying the topics surrounding the news articles and unveiling the ideological implications embedded in the news articles. 1520 news articles from China Daily, the official English-language newspaper in China, were collected and analyzed through keyword analysis and concordance analysis. The findings reveal that three topics exist in the news articles, with social & economic matters ranking first, followed by national/regional entity and social identity. It is also found that three ideologies, including collectivism, gender-essentialism and economic development centered ideology are manifested in the coverage of China’s family planning policy. This study sheds light on the ideological underpinnings on the reportage of the policies and how these policies are represented to address the population issues, revealing how language used in newspapers facilitates the promotion of national policies and reinforcement of official ideologies through topic selection and presentation.